Acetaminophen-Induced Liver Injury Alters the Acyl Ethanolamine-Based Anti-Inflammatory Signaling System in Liver - Rivera, Patricia; Pastor, Antoni; Arrabal, Sergio; Decara, Juan; Vargas, Antonio; Sánchez-Marín, Laura; Pavón, Francisco J.; Serrano, Antonia; Bautista, Dolores; Boronat, Anna; de la Torre, Rafael; Baixeras, Elena; et al. (Frontiers in Pharmacology, 2017)
Protective mechanisms against drug-induced liver injury are actively being searched to identify new therapeutic targets. Among them, the anti-inflammatory N-acyl ethanolamide (NAE)-peroxisome proliferators activated receptor alpha (PPARα) system has gained much interest after the identification of its protective role in steatohepatitis and liver fibrosis. An overdose of paracetamol (APAP), a commonly used analgesic/antipyretic drug, causes hepatotoxicity, and it is being used as a liver model. In the present study, we have analysed the impact of APAP on the liver NAE-PPARα system. A dose-response (0.5-5-10-20 mM) and time-course (2-6-24 hours) study in human HepG2 cells showed a biphasic response, with a decreased PPARα expression after 6-hour APAP incubation followed by a generalized increase of NAE-PPARα system-related components (PPARα, NAPE-PLD, and FAAH), including the NAEs oleoyl ethanolamide (OEA) and docosahexaenoyl ethanolamide, after a 24-h exposure to APAP. These results were partially confirmed in a time-course study of mice exposed to an acute dose of APAP (750 mg/kg). The gene expression levels of Pparα and Faah were decreased after 6 hours of treatment and, after 24 hours, the gene expression levels of Nape-pld and Faah, as well as the liver levels of OEA and palmitoyl ethanolamide, were increased. Repeated APAP administration (750 mg/kg/day) up to 4 days also decreased the expression levels of PPARα and FAAH, and increased the liver levels of NAEs. A resting period of 15 days completely restored these impairments. Liver immunohistochemistry in a well-characterized human case of APAP hepatotoxicity confirmed PPARα and FAAH decrements. Histopathological and hepatic damage (Cyp2e1, Caspase3, αSma, Tnfα, and Mcp1)-related alterations observed after repeated APAP administration were aggravated in the liver of Pparα-deficient mice. Our results demonstrate that the anti-inflammatory NAE-PPARα signaling system is implicated in liver toxicity after exposure to APAP overdose, and may contribute to its recovery through a long-term time-dependent response.